Lift every voice : Radford University teacher education students - Ellis, Antonio L.; Grillo, Lisa Maria; Hutchinson, Jania; Ayers, William Bill (Urban education studies., 2024)
"Radford University was founded as a Normal School for teachers in 1910 and has remained a leader in teacher education ever since. Today, the School of Teacher Education and Leadership is defined by our strong partnerships with public schools and our diverse programs that prepare teachers and administrators to serve children from birth through high school. The voices of undergraduate students are often silenced and omitted from scholarly literature beyond serving participants in research studies. This volume legitimizes the voices and life experiences of Radford University undergraduate teacher education students as emerging authorities on the subject of teacher education. Contributors employ a critical storytelling methodology to illuminate the ways in which classroom practices of teachers impacted them academically, socially, and emotionally. The editor hope that these stories, anecdotes, and analysis will be valuable to preservice and classroom teachers who are engaged in educating Pre-K through 12 students"--